Remission from Chronic Anorexia Nervosa With Ketogenic Diet and Ketamine: Case Report - Barbara Scolnick; Beth Zupec-Kania; Lori Calabrese; Chiye Aoki; Chiye Aoki; Thomas Hildebrandt (Frontiers in Psychiatry, 2020)
BackgroundChronic anorexia nervosa is a tragic disease with no known effective pharmacological or behavioral treatment. We report the case of a 29 year-old woman who struggled with severe and enduring anorexia nervosa for 15 years, and experienced a complete recovery following a novel treatment of adopting a ketogenic diet followed by ketamine infusions. Her remission has persisted for over 6 months.Case PresentationAt age 14.5, the patient embarked on an effort to “eat healthy.” She quickly lost control of the dieting, developed associated compulsions and obsessions about food, body dissatisfaction, emotional lability, and lost nearly 13.6 kilograms (30 pounds). She was hospitalized for 6 weeks, and while she regained some weight, she did not attain full weight restoration. For 15 years, she continued to eat in a restrictive manner, exercise compulsively, and have intermittent periods of alcohol dependence. Nevertheless, she always hoped to get well, and at age 29, she began a novel treatment for anorexia nervosa.ConclusionsThis is the first report of a ketogenic diet used specifically for the treatment of anorexia nervosa, followed by a short series of titrated IV ketamine infusions leading to complete remission of severe and enduring anorexia nervosa, with weight restoration, and sustained cessation of cognitive and behavioral symptoms, for 6 months. Although these treatments were used sequentially the relationship between these modalities, and possible synergy, is unclear, and deserves further study. Complete and sustained remission of chronic anorexia nervosa is quite rare, and the novel use of a ketogenic diet and IV ketamine treatment in this potentially lethal condition suggests avenues for further research, and hope for patients and their families.